Holographic Video Conferencing for Fostering Communication and Participation: Pre-Conceptualization of Focus Group of Female Learners in Arab Open University (KSA) - M. Aman, Abdulrazak; Shiratuddin, Norshuhada (International Journal of Engineering and Technology, 2018)
Educational institutes are quick to take benefits of technological facilities through incorporating ICT into education, particularly for female students in Saudi education system due to the imposed religious barriers, which sequentially has produced innovative models of education such as, distance learning and blended learning. Deriving from this, holographic video conference (HVC) is considered to be a new tool for better achievement with respect to communication and participation of female students at Arab Open University in Saudi Arabia. This phenomenon makes it progressively important to understand factors impacting it. The study will use design science research (DSR) as a research paradigm that will create and evaluate information technology (IT) artifacts proposed in this research to explain recognized female studentsâ€™ problems.Â DSR model includes five phases which are: awareness of problem, suggestion, development, evaluation and conclusion. The proposed research method will be used to determine the perceptions of female learners towards HVC. Using this technique, the effectiveness of HVC in regards to participation and communication of female learners with the male instructors will be determined.